Genomic Mapping, Molecular Marker and Marker Assisted Selection in Rice: A Review - Takele Mitiku Abdeta; Wakuma Biratu; Lemi Yadesa (Agro Bali : Agricultural Journal, 2022)
Increased agricultural output is necessary to feed a growing world population, yet crop yield growth rates are currently slowing down. Therefore, qualities related to yield, stability, and sustainability should take center stage in plant breeding initiatives. Durable disease resistance, abiotic stress tolerance, and effective nutrition and water usage are a few of these characteristics. On several rice chromosomes, various resistance genes have been discovered, mapped, and tightly connected DNA markers have been created. The following qualities were chosen as potential molecular marker candidates: fragrance, disease resistance to bacterial, blast, and sheath blights, grain extension while cooking, chalkiness propensity, gelatinization temperature, minor aroma components, and seedling vigor/early establishment. With the help of developments in genetics and genomics, it is now feasible to go into the history of rice domestication and identify the precise genetic processes that were influenced by human selection. Agronomic main effect quantitative trait loci (QTLs) may contribute cumulatively to genetic variation, with hybrids showing stronger effects and comparatively fewer contributions from epistatic effects.